ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PASIEN PADA PELAYANAN FARMASI DI RUMAH SAKIT JIWA MUTIARA SUKMA MATARAM - Ulfatul Uyun; Muhammad Habibullah Aminy; Slamet Mardiyanto Rahayu; Lale Ajeng Khalifatun Wardani; Wahyu Aprilyaningsih (Nusadaya Journal of Multidiciplinary Studies, 2024)
This study aimed to analyze the factors influencing patient satisfaction with pharmaceutical services at Rumah Sakit Jiwa Mutiara Sukma Mataram. A quantitative approach was employed, utilizing multiple linear regression analysis to examine the effects of service promptness (X1), accuracy of medication dispensing (X2), and clarity of drug-related information (X3) on patient satisfaction (Y). The results of the partial hypothesis testing (t-test) indicated that all three independent variables had a positive and statistically significant effect on patient satisfaction, with respective significance values of 0.028, 0.046, and 0.040 (p < 0.05). Simultaneously, the F-test results demonstrated that these variables collectively exerted a significant effect on patient satisfaction, with a significance value of 0.012 (p < 0.05). The coefficient of determination (R²) was 0.840, indicating that 84.00% of the variance in patient satisfaction can be explained by service promptness, accuracy of medication dispensing, and clarity of drug information, while the remaining 16.00% is attributable to other factors beyond the scope of the research model. Enhancing the quality of pharmaceutical services through the optimization of these three aspects represents a relevant and strategic approach to improving patient satisfaction.